Lipid profiles in wheat cultivars resistant and susceptible to tan spot and the effect of disease on the profiles - Kim, Dongwon; Jeannotte, Richard; Welti, Ruth; Bockus, William W. (My University, 2012)
Lipid profiles in wheat leaves and the effects of tan spot on the profiles were quantified by mass spectrometry. Inoculation with Pyrenophora tritici-repentis significantly reduced the amount of leaf lipids, including the major plastidic lipids monogalactosyldiacylglycerol (MGDG) and digalactosyldiacylglycerol (DGDG), which together accounted for 89% of the mass spectral signal of detected lipids in wheat leaves. Levels of these lipids in susceptible cultivars dropped much more quickly during infection than those in resistant cultivars. Furthermore, cultivars resistant or susceptible to tan spot displayed different lipid profiles; leaves of resistant cultivars had more MGDG and DGDG than susceptible ones, even in noninoculated plants. Lipid compositional data from leaves of 20 noninoculated winter wheat cultivars were regressed against an index of disease susceptibility and fitted with a linear model. This analysis demonstrated a significant relationship between resistance and levels of plastidic galactolipids and indicated that cultivars with high resistance to tan spot uniformly had more MGDG and DGDG than cultivars with high susceptibility. These findings suggest that lipid composition of wheat leaves may be a determining factor in the resistance response of cultivars to tan spot.
Citation: Kim, D., . . . & Bockus, W. (2012). Lipid Profiles in Wheat Cultivars Resistant and Susceptible to Tan Spot and the Effect of Disease on the Profiles. Phytopathology, 103(1), 74-80. https://doi.org/10.1094/PHYTO-05-12-0099-R
Keywords: Wheat; Tan spot; Lipid composition of wheat leaves